2017
DOI: 10.2147/ijwh.s150064
|View full text |Cite
|
Sign up to set email alerts
|

Impact of patient demographics, tumor characteristics, and treatment type on treatment delay throughout breast cancer care at a diverse academic medical center

Abstract: Purpose and objectiveThe aim of this study was to examine the impact of patient demographics, tumor characteristics, and treatment type on time to treatment (TTT) in patients with breast cancer treated at a safety net medical center with a diverse patient population.Patients and methodsA total of 1,130 patients were diagnosed and treated for breast cancer between 2004 and 2014 at our institution. We retrospectively collected data on patient age at diagnosis, race/ethnicity, primary language spoken, marital sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…As for the reviews that reported no association between young age and delay, two of them found significant crude associations that then disappeared when controlling by symptom presentation [6, 47], menstrual status [47] and history of benign breast conditions [47], which are all related with young age. The remaining negative studies defined young age as < 50 years, had a small sample size (n = 380) or focused on women identified through screening mammography [48], which could be the reasons they did not find a significant association between age and delay. It could also be that this relationship is different in diverse health system contexts.…”
Section: Delays In Diagnosis Among Young Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the reviews that reported no association between young age and delay, two of them found significant crude associations that then disappeared when controlling by symptom presentation [6, 47], menstrual status [47] and history of benign breast conditions [47], which are all related with young age. The remaining negative studies defined young age as < 50 years, had a small sample size (n = 380) or focused on women identified through screening mammography [48], which could be the reasons they did not find a significant association between age and delay. It could also be that this relationship is different in diverse health system contexts.…”
Section: Delays In Diagnosis Among Young Womenmentioning
confidence: 99%
“…On the other hand, only three quality studies have analysed the effect of young age on the treatment interval (time between diagnosis confirmation and cancer treatment initiation) and also showed contradictory results. One found an increased risk of delayed treatment among younger women [49], another reported a decreased risk in this group [46] and the last one found no association [48].…”
Section: Delays In Diagnosis Among Young Womenmentioning
confidence: 99%
“…The landmark 2003 Institute of Medicine report Unequal Treatment noted that racial and ethnic minorities continue to receive lower quality health care in comparison with nonminorities, even when controlling for factors relating to access [1]. For example, although African American women have a lower overall incidence of breast cancer than white women, they are more likely than white women to be diagnosed with cancer at a more advanced stage, have a more aggressive form of cancer, and have higher rates of mortality from breast cancer [16,17]. Here, radiologists can have an active role in recognizing barriers to care in vulnerable populations and acting as agents of change.…”
Section: Arguments For Diversity and Inclusionmentioning
confidence: 99%
“…Race/Ethnicity disparities have been shown to impact delays in diagnosis and treatment. 12,13 In women aged ,50 years, Black women experienced greater delays than White women. 14 Similar findings have been seen in patients of older age, those who are unmarried, or those from a lower socioeconomic background.…”
Section: Introductionmentioning
confidence: 99%